CHEMICAL FOUNDATIONS OF HORMONE ACTION AND HORMONAL RECEPTORS (American Journal of Technology and Applied Sciences, 2025)
Hormones are biologically active chemical substances that regulate virtually all physiological processes in the human body—including growth, metabolism, reproduction, stress responses, and the maintenance of homeostasis. Their action is based on the highly selective interaction between a hormone and its specific receptor, which triggers a cascade of intracellular signaling events. This article examines the chemical nature of various classes of hormones, the mechanisms of receptor binding, the main types of hormonal receptors, and the pathways of intracellular signal transduction. Particular attention is given to the role of hormone–receptor interactions in metabolic regulation, as well as their significance for the diagnosis and treatment of endocrine disorders.